Qualitative Study to Identify Preventive Components of Family Collapse - Arami, Hossein; Shafiabadi, Abdollah; Zahrakar, Kianoush (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to developed a model for preventing family collapse based on the knowledge and experience of some experts and couples applying for the divorce. Methods: The research method was qualitative with the grounded theory technique. Results: The results were obtained based on three stages of coding with more than 205 meaningful propositions, 404 corresponding concepts, 35 sub-categories, 12 main categories, and one core category. Conclusion: The 12 categories obtained include an emphasis on continuous education, economic strengthening, legal support for a healthy life, skill training and skill enhancement, continuous moral reproduction, cultural immunity, healthy lifestyle, rational choice, strengthening the internal links of members, building mutual trust, family orientation, and effective intervention. Abstracting these categories in the selective coding stage obtained a core category called " Prevention of family collapse leads to the consequences of strengthening internal bonds, healthy lifestyle and family orientation due to mutual trust building, continuous moral reproduction in the context of economic strengthening, the effective intervention of culture, rationality with educational and skill strategies combined with legal protection of healthy life "which can cover all the topics of the participants.